Three-dimensional reconstructions of nucleolus-organizing regions in PHA-stimulated human lymphocytes - Hozák, P; Novák, J T; Smetana, K (Biology of the cell, 1989)
Ultrastructure and three-dimensional distribution of nucleolus-organizing regions have been studied on ultrathin serial sections of PHA-stimulated human lymphocytes. During the 48 hr of activation the size of fibrillar centers (FCs) decreased from 0.6-0.9 microns to 0.2-0.3 microns and the number of FCs increased rapidly from one to 75-107 per cell. The number of fibrillar complexes (i.e. associations of a different number of FCs connected by the dense fibrillar component) also increased but did not reach the maximum number of nucleolar organizers presented here. Three-dimensional computer reconstructions of fibrillar complexes showed that lymphocyte activation was accompanied by early (2-4 hr) changes in the shape of the primary fibrillar center. Invagination of the dense fibrillar component on its surface occurred and division into two or more smaller FCs followed. Gradually, the typical structure of the nucleolus with several fibrillar complexes and many FCs was formed. These results confirm the hypothesis of fibrillar complex-nucleolar organizer correlation published recently.
Keywords: Phytohemagglutinins; Time Factors; časové faktory; Humans; aktivace lymfocytů; organizátor jadérka; lidé; T-lymfocyty; Lymphocyte Activation; T-Lymphocytes; fytohemaglutininy; Nucleolus Organizer Region; Microscopy, Electron; elektronová mikroskopie